Systematic observation of healthy eating environments in after-school services: a cross-sectional study. Issue 18 (5th December 2021) - Crowe, Ruth K; Probst, Yasmine; Weaver, R Glenn; Beets, Michael W; Kemp, Byron; Stanley, Rebecca M; Okely, Anthony D
Abstract: Objectives: Few studies have examined the healthy eating environments within the Australian out of school hours care (OSHC) setting. This study aims to describe healthy eating environments, consisting of: (a) the alignment of provided food and beverages to Australian Dietary Guidelines; (b) healthy eating promotion practices; (c) nutrition education through cooking experiences; (d) staff role modelling healthy eating and (e) regular water availability. Design: A cross-sectional study was conducted using direct observations and the validated System for Observing Staff Promotion of Activity and Nutrition (SOSPAN) tool. Setting: OSHC located in urban and semi-rural regions of NSW, Australia. Participants: Staff (151) and children (1549) attending twelve OSHC services operating in the hours after school. Results: Fifty per cent (50 %) of services offered fruits and 100 % offered water as a part of the afternoon snack on all four observation days. Discretionary foods were offered on more days compared to vegetables (+1·9/d, P = 0·009), lean meats (+2·7/d, P =·0 004) and wholegrains (+2·8/d, P = 0 002). Staff promoted healthy eating on 15 % of days, sat and ate with children 52 %, consumed high sugar drinks 15 % and ate discretionary foods in front of children 8 % of days, respectively. No opportunities for cooking or nutrition education were observed. Conclusion: Afternoon snacks regularly contained fruits and water. Opportunities exist to improve the frequency by which vegetables, wholegrains and lean meats are offered in addition to staff healthy eating promotion behaviours. Future research is warranted to further explore healthy eating behaviours, practices and policies within the after-school sector.